The Effect of Wheat Starch Addition Level on Moisture Content, Fat Content, Protein Content, Microstructure, and Organoleptic Quality of Processed Gouda Cheese - Eka Fitasari (Faculty of Animal Science Universitas Brawijaya, 2009)
The research was conducted to find out the optimum level of wheat starch to produce processed cheese with good quality based on its moisture content, fat content, protein content, microstructure, and organoleptic quality. The result showed that the different level of wheat starch gave highly significant effect (p<0.01) on moisture content, fat content, protein content, and panelist preference to texture, taste, and smell. It is concluded that wheat starch decrease moisture content, fat content, protein content, and panelist preference to texture, taste and smell processed Gouda cheese. It is suggested to add 10 % wheat starch to produce processed cheese because the product met the existing standard of commercial product chemically and physically, except fat content and protein content. Further research on the production of processed cheese is suggested by adding fat and protein sources to meet the standard of fat and protein content. Â Keywords : processed cheese, wheat starch